Severe fever and thrombocytopenia syndrome virus infection: Considerations for vaccine evaluation of a rare disease - Joel N. Maslow; Jackie J. Kwon; Susan K. Mikota; Susan Spruill; Youngran Cho; Moonsup Jeong (Taylor & Francis Group, 2019)
Infection caused by the severe fever and thrombocytopenia syndrome virus (SFTSV) causes a hemorrhagic illness with a mortality between 20% and 40%. Initially recognized in 2009 in China, cases have additionally been documented in Japan and Korea although retrospective studies have documented seroprevalence since 1996. Although case rates have increased due to increased awareness and more widely available diagnostics, SFTSV infection remains rare with the highest rates documented in Korea for Jeju Province (3.5 cases per 100,000 population) and the Inje-gun region (66.2 cases per 100,000). Because of the very low incidence of infection, a placebo-controlled study with 1:1 randomization to evaluate an SFTSV vaccine would require a sample size that is 25% greater than the region of study. We discuss alternatives to licensure. Vaccine effectiveness may be assessed through a registry, comparing rates of infection over time between vaccine recipients versus regional populations. Modeled data can be updated based on actual case rates and population changes over the years of follow-up. Using one model, statistically significant differences are seen after 10 years in Inje-gun and 15 years of follow-up in Jeju. This approach may be applicable to other uncommon infectious diseases for which a standard study design is difficult.